A Simple Surgical Technique for Subpectoral Biceps Tenodesis Using a Double-Loaded Suture Anchor - Scully, William F. (Elsevier, 2013)
Multiple different surgical techniques have previously been described to address long head of the biceps tendinopathy. Subpectoral biceps tenodesis has proven to be an effective procedure to relieve pain and maintain function. We describe a surgical technique for subpectoral biceps tenodesis using a single double-loaded suture anchor implant. Advantages of this procedure include the ease of implant placement and the freedom this technique affords to perform the anchor placement without direct visualization of the docking site.